2003
DOI: 10.1177/154193120304702011
|View full text |Cite
|
Sign up to set email alerts
|

Viewpoint Optimisation for Virtual Environment Navigation Using Dynamic Tethering - A Study of Tether Rigidity

Abstract: Much research has been carried out on providing navigational aids and improving users' wayfinding ability across a variety of navigation related tasks. In this study, we focus on investigating users' navigational performance with respect to the display frame of reference in a large scale virtual environment. Dynamic viewpoint tethering is proposed as a means to improve user control and reduce the need for mental rotations, thus facilitating the acquisition of configurational knowledge about the virtual space. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…As a framework for constraining viewpoint behaviour in navigational display systems, viewpoint tethering has been proposed in recent years as a means of integrating information from both egocentric and exocentric frames of reference (McCormick et al, 1998;Colquhoun & Milgram, 2000;Wang & Milgram, 2001;2002;2003). The concept of viewpoint tethering encompasses a display design technique that involves using a tether for virtually "attaching" the display viewpoint to an avatar.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a framework for constraining viewpoint behaviour in navigational display systems, viewpoint tethering has been proposed in recent years as a means of integrating information from both egocentric and exocentric frames of reference (McCormick et al, 1998;Colquhoun & Milgram, 2000;Wang & Milgram, 2001;2002;2003). The concept of viewpoint tethering encompasses a display design technique that involves using a tether for virtually "attaching" the display viewpoint to an avatar.…”
Section: Introductionmentioning
confidence: 99%
“…Wang & Milgram (2001) extended the experimental domain into 3D and, in a virtual tunnel navigation scenario, they found that tethered displays supported superior tracking performance relative to both ego-and exo-centric displays. In follow-up studies, Wang & Milgram (2002;2003) contrasted tethered displays with different dynamic properties and showed that a critically damped dynamically tethered display resulted in the best guidance performance. In the study reported here, efforts have been focused on investigating the effect of viewpoint viewing distance, in terms of the tether length, on both local guidance and global awareness performance in a navigational scenario.…”
Section: Introductionmentioning
confidence: 99%